Talavija līdzās Latvijai - Rubenis, Rūdolfs; Počs, Marģers; Latvijas Universitātes Muzejs (My University, 2020)
Virtuālā izstāde “Talavija līdzās Latvijai” ir strukturēta tematiskā formā ar hronoloģisku ievirzi, izceļot spilgtākos notikumus un personības Latvijas vēsturē no 1918. gada līdz mūsdienām, kur īpaša loma bijusi atvēlēta 1900. gada 14. decembrī pie Rīgas Politehniskā institūta dibinātajai latviešu studentu korporācijai Talavija. Notikumi un personības atspoguļotas ar fotoliecībām no Talavija arhīva un Latvijas Universitātes Muzeja krājuma.

The virtual exhibition “Talavija next to Latvia” is structured in a thematic form with a chronological orientation, highlighting the brightest events and personalities in the history of Latvia from 1918 to the present day, where the Latvian student corporation Talavija, founded on December 14, 1900 at Riga Polytechnic Institute, played a special role. The events and personalities are depicted with photo testimonials from the Talavija archive and the collection of the Museum of the University of Latvia.
Talavija next to Latvia
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Talavija; studentu akadēmiskā mūža organizācija; Latvija; student corporation; Latvia